Hate crime offending among European youth: prevalence and risk factors - Kaakinen, Markus (European journal of criminology, 2025)
Crime motivated by hate toward social groups and identities is a major social problem. Due to the rise of interethnic, ideological, and religious tensions, the criminal policy relevance of this crime has increased. One compelling question for hate crime researchers has been whether hate crime is different from general crime. In this study, we draw on the most recent available comparative European dataset, the third sweep of the International Self-Report Delinquency Study (N = 34,871), to explore the extent and correlates of hate crime offending across sampled urban youth populations from 17 European countries. We find that 2.5% of 12–16-year-olds reported involvement in a hate crime. Country rates range from 0.7% to 6.5%, with the lowest figures observed in Western Europe and the highest figures observed in Southeast Europe. The individual-level risk factors of hate crimes tend to be the same as in other offending, thus supporting general rather than specific causation. However, some evidence suggests that some risk factors were particularly strongly associated with committing hate-motivated crimes: disorder in neighborhood, risky routines, discriminatory attitudes, low self-control and propensity to feel shame, lifetime delinquency, male gender, and hate crime victimization. Country-level differences in the studied individual-level risk factors only partly explained the differences between urban youth populations in the prevalence of hate crime, thus indicating national-level contextual effects that should be further explored in future research. As our data are based on city-level samples rather than full national populations, these findings should be interpreted as reflecting differences between urban areas in different countries rather than nationwide patterns.